Chemistry novice teachers’ professional knowledge, know-how and the support needs in professional development - Handolin-Kiilo, Heidi (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
This article discusses the knowledge, know-how and the support needs of the chemistry teachers’ during their first years of teaching. Finnish chemistry teacher education gives its students an academic education, qualification to teach and at the same time equipment for lifelong learning. The construction of teachers’ knowledge and know-how is especially based on the Grossman theory model. This article is based on a licentiate thesis, which deals with chemistry teacher graduates of first years of expertise in the schools and the challenges of the work and the needs for support. Research information on chemistry subject teachers’ knowledge and wellbeing at their profession and at the school community is needed when developing relevant chemistry subject teacher education. Knowledge and research information of the possible support needs in professional development is also needed when developing forms of aid and supporting novice teachers (beginning teachers) to stay in the profession of teaching, continuous life-long learning, professional knowledge and know-how.